2012
DOI: 10.1021/jp309636m
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Enhancement of Organic and Thin-Film Silicon Solar Cells with Photochemical Upconversion

Abstract: The efficiency of thin-film solar cells with large optical band gaps, such as organic bulk heterojunction or amorphous silicon solar cells, is limited by their inability to harvest the (infra)red part of the solar spectrum. Photochemical upconversion based on triplet–triplet annihilation (TTA-UC) can potentially boost those solar cells by absorbing sub-bandgap photons and coupling the upconverted light back into the solar cell in a spectral region that the cell can efficiently convert into electrical current. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
202
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 166 publications
(204 citation statements)
references
References 44 publications
2
202
0
Order By: Relevance
“…Indeed we have found that this model describes the measured QE data of TTA-UC-enhanced solar cells of various types very well, as can be seen for the example of a P3HT:ICBA organic bulk heterojunction solar cell 95 in Fig. 7.…”
Section: Analysis Schemesupporting
confidence: 62%
See 3 more Smart Citations
“…Indeed we have found that this model describes the measured QE data of TTA-UC-enhanced solar cells of various types very well, as can be seen for the example of a P3HT:ICBA organic bulk heterojunction solar cell 95 in Fig. 7.…”
Section: Analysis Schemesupporting
confidence: 62%
“…91 For a useful review on upconversion nanophosphors for solar cell applications, see the recent review of Ramasamy et al 92 In 2012, our group demonstrated the first solar cell assisted by triplet-triplet annihilation upconversion, using the example of an amorphous silicon thin-film solar cell. 47,93,94 The approach was successively applied to organic solar cells 95 as well as dye-sensitized solar cells. 96 Details about these results and a comparison to the lanthanoid upconversion system are given below.…”
Section: Photonic Upconversionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, tremendous advancements have been achieved in photochemical upconversion by using metal-containing triplet sensitizers with a variety of organic-based triplet acceptors/annihilators in both fluid solution [20,22,[29][30][31][32] and various host matrices [33][34][35][36][37][38][39][40][41][42][43]. The ultimate goal of this research is to maximize the efficiency of real-world solar powered devices by imparting sub-bandgap sensitization via integration of UC technology [8][9][10]44,45]. This change in cell design should reduce the drastic losses owing to spectral mismatch between various sensitizers and semiconductor bandgaps.…”
Section: Introductionmentioning
confidence: 99%